2022
DOI: 10.3390/diagnostics12030616
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Different Techniques for Improving the Treatment of Pulmonary Hypertension Secondary in Systemic Sclerosis Patients

Abstract: In systemic sclerosis (SSc) mortality is mainly linked to lung involvement which is characterized by interstitial lung disease (ILD) and pulmonary hypertension (PH). In SSc, PH may be due to different etiologies, including ILD, chronic thromboembolic disease, pulmonary veno-occlusive disease, and pulmonary arterial hypertension (PAH). The main tool to screen PAH is transthoracic echocardiography (TTE), which has a sensitivity of 90%, even if definitive diagnosis should be confirmed by right heart catheterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 81 publications
0
23
0
Order By: Relevance
“…A major improvement of treatment strategies based on pathophysiology have been made in the past 20 years; however, CTD-PAH remains a progressive disease resulting in RHF and eventually death. 6,7 Factors associated with poor prognosis in PAH have been reported, including World Health Organization functional class (WHO-FC) III/IV, a risk of syncope, high right atrial pressure and low cardiac index in hemodynamics, as well as signs of multisystem organ failure. 8 In terms of CTD-PAH, we previously identified the 6-munite walking distance ≤380 m and underlying CTD were independent predictors of mortality in a Chinese cohort.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A major improvement of treatment strategies based on pathophysiology have been made in the past 20 years; however, CTD-PAH remains a progressive disease resulting in RHF and eventually death. 6,7 Factors associated with poor prognosis in PAH have been reported, including World Health Organization functional class (WHO-FC) III/IV, a risk of syncope, high right atrial pressure and low cardiac index in hemodynamics, as well as signs of multisystem organ failure. 8 In terms of CTD-PAH, we previously identified the 6-munite walking distance ≤380 m and underlying CTD were independent predictors of mortality in a Chinese cohort.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Although with high heterogeneity, the outcomes of patients with CTD‐PAH are extremely poor. A major improvement of treatment strategies based on pathophysiology have been made in the past 20 years; however, CTD‐PAH remains a progressive disease resulting in RHF and eventually death 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several studies have shown that PH subtypes other than group 1 may occur in the setting of CTDs, and discriminating between the different aetiologies can pose a challenge for clinicians. For instance, in SSc, groups 2, 3 and 4 PH must be considered for the differential diagnosis once PAH is suspected [ 176 ]. Differentiating SSc-PAH from PH-ILD is particularly difficult due to the high prevalence of ILD in SSc, and to the fact that both entities show a pre-capillary pattern in RHC; however, since the prognosis and the treatment of these two conditions differ radically, it is of the utmost importance to make the correct diagnosis at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a chronic condition characterized by proliferative vasculopathy in which structural changes of the pulmonary vascular lead to hemodynamic changes and right ventricular failure [ 1 , 2 , 3 ]. The currently approved therapies target three pathways involved in endothelial dysfunction—the prostacyclin and nitric oxide (NO) pathways, which are impaired in PAH patients, and the endothelin pathway, which is overactivated in these patients.…”
Section: Introductionmentioning
confidence: 99%